The dialectics of the religious and the secular: studies on the future of religion - Ott, Michael R. ca. 20./21. Jh. (Studies in critical social sciences 1573-4234, 2014)
In The Dialectics of the Religious and the Secular , fifteen international scholars address the question of the relevancy, meaning, and future of religion within the increasing antagonisms between the religious and secular realms of modern civil society and its globalization